Techniques and complications of breast augmentation: a literature review (Research, Society and Development, 2023)
According to the International Society of Aesthetic Plastic Surgery, Brazil has the highest rate of plastic surgeries in the world. Following the world standard, breast augmentation is one of the most common cosmetic procedures in Brazil, being considered one of the safest procedures with the highest efficiency rate. This review aims to analyze the techniques and risks of breast augmentation. For the elaboration of the work, the integrative bibliographic review methodology was used. Regarding the surgical technique, two surgical methods are used to locate the implant, the subglandular and submuscular methods, with three options for incision methods: inframammary, periareolar and axillary for incision. it is essential to achieve the aesthetic and functional objective desired by the patient. Currently, implants are divided between anatomical shape and round shape, with the round being divided into 3 subtypes: round with high profile, round with super-high profile and round with low profile. In every surgical procedure there is a risk of complications, with ASIA syndrome, infection and seroma being the most common in mammoplasty. From the present study, it is possible to observe that there are several techniques for performing the silicone implant and when choosing, the plastic surgeon must take the technical criteria proven in the medical literature and the patient's desire.